2023
DOI: 10.1111/joim.13685
|View full text |Cite
|
Sign up to set email alerts
|

Readmission and inhospital death 1 year after COVID‐19 hospitalization in South Africa

Abstract: BackgroundAcute SARS‐COVID‐19 infection may increase readmission risk compared to other respiratory infections. We assessed the 1‐year readmission and inhospital death rates of hospitalized SARS‐COVID‐19 patients compared to patients hospitalized with other types of pneumonia.MethodsWe determined the 1‐year readmission and inhospital death rate of adult patients initially hospitalized with a positive SARS‐COVID‐19 result, and subsequently discharged, between March 2020 and August 2021, at a Netcare private hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…The Mexican cohort in this study had a high prevalence of comorbidities, including hypertension (20%), diabetes (16%), and obesity (19%), among patients with COVID‐19. These findings are consistent with previous research on adults in the United States, which has shown that individuals with diabetes are at an increased risk of severe illness and complications from COVID‐19 31 …”
Section: Discussionsupporting
confidence: 92%
“…The Mexican cohort in this study had a high prevalence of comorbidities, including hypertension (20%), diabetes (16%), and obesity (19%), among patients with COVID‐19. These findings are consistent with previous research on adults in the United States, which has shown that individuals with diabetes are at an increased risk of severe illness and complications from COVID‐19 31 …”
Section: Discussionsupporting
confidence: 92%